Elliott the otter : the totally untrue story of Elliott Boss of the Bay - Skewes, John; Ode, Eric (Little Bigfoot, an imprint of Sasquatch Books, 2015)
"Elliott the otter lives in Puget Sound's Elliott Bay and claims it's named after him. And why wouldn't it be, since he's in charge of its daily activity? From the freighters bringing in cargo from around the world to the salmon passing through on their way upstream, Elliott is the boss of it all"--